Numerical simulation of liquefaction-related phenomena - Azeiteiro, Ricardo José Novo (2021)
Thesis for the degree of Doctor of Philosophy in Civil Engineering, specialisation in Geotechnics, submitted to the Department of Civil Engineering of the Faculty of Sciences and Technology of the University of Coimbra.